2011
DOI: 10.1097/aci.0b013e3283445939
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides and asthma

Abstract: Many pesticides are sensitizers or irritants capable of directly damaging the bronchial mucosa, thus making the airway very sensitive to allergens or other stimuli. However, most pesticides are weakly immunogenic so that their potential to sensitize airways in exposed populations is limited. Pesticides may increase the risk of developing asthma, exacerbate a previous asthmatic condition or even trigger asthma attacks by increasing bronchial hyper-responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 42 publications
4
95
0
1
Order By: Relevance
“…According to this review, the main mechanism lies in the neurogenic inflammation induced by contact with pesticides in agricultural populations. In the case of asthma induced by organophosphates, the problem seems to be a dysfunction in muscarinic M2 receptors, which are normally used to limit the release of acetylcholine esterase by parasympathetic fibres [69].…”
Section: Discussionmentioning
confidence: 99%
“…According to this review, the main mechanism lies in the neurogenic inflammation induced by contact with pesticides in agricultural populations. In the case of asthma induced by organophosphates, the problem seems to be a dysfunction in muscarinic M2 receptors, which are normally used to limit the release of acetylcholine esterase by parasympathetic fibres [69].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HERNÁNDEZ et al [15] have drawn attention to experimental studies suggesting a potential relationship between induced airway hyperreactivity in allergic asthma and pesticide exposure. PROSKOCIL et al [16] have reported a lower potentiated vagally induced bronchoconstriction threshold in allergen sensitised guinea pigs, and increased production of proinflammatory cytokines in guinea pigs induced by organophosphate insecticides [17].…”
Section: Introductionmentioning
confidence: 99%
“…The frequent use of bleach (hypochlorite), ammonia, and degreasing sprays has been consistently associated with asthma among workers exposed to cleaning agents (42,44,48), although the precise chemical exposures and the mechanisms responsible for the increased incidence of asthma have not been clarified since cleaning materials typically contain a wide variety of ingredients, some of which are respiratory irritants, while others are potential airway sensitizers (Table 6). Other occupations associated with increased risk of asthma that cannot be readily or completely explained on the basis of a clear sensitizing exposure are presented in Table 6 (47,(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Epidemiological Evidence For Irritant-induced Asthmamentioning
confidence: 99%